ANALYSIS AND MAPPING OF SEISMIC HAZARD AT SURFACE BASED ON SUBDUCTION AND FAULTS SOURCES IN THE JAVA AND MADURA ISLAND REGION - Wallansha, Robby
Infrastructure development in several regions in Indonesia has increased every year. Some areas in Java and Madura have the largest budget allocations for infrastructure development, which is followed by increasing population and economic growth in these regions. However, there is a high earthquake disaster threat in Java and Madura, supported by a history of damaging earthquakes in the study area. Disaster mitigation studies need to be carried out to minimize material and immaterial losses, one of which is through seismic hazard mapping. PSHA (Probabilistic Seismic Hazard Analysis) method is one approach to seismic hazard analysis utilizing probability distribution related to the scale, location, and frequency of earthquake events. Seismic hazard mapping using the PSHA method has been widely conducted in Indonesia. However, these mappings have not involved Vs30 data, thus only representing values at the bedrock level. This differentiates the current study from previous research, as it represents surface values. This study uses several data sets, including earthquake source data, shear wave velocity data up to 30 meters, and reference GMPE (Ground Motion Prediction Equation) models. Earthquake source data include fault and subduction source parameter models based on previous studies, while Vs30 data are based on technical geomorphology data. Seismic hazard maps produced for a 2% probability of exceedance in 50 years at PGA, 0.2-second, and 1-second periods are represented by PGA (Peak Ground Acceleration) values. These maps include seismic hazard maps at bedrock, seismic hazard maps at surface, and amplification maps. Seismic hazard maps at bedrock for PGA, 0.2-second, and 1-second periods show PGA values that spatially increase towards the south of Java and Madura. PGA value ranges for these three periods are 0.1 – 1.1 g, 0.2 g – 2.5 g, and 0.1 g – 2.0 g, respectively. The areas with the lowest PGA values are generally located in the northern part of Java and the western part of Madura, with PGA values ranging from 0.1 g – 0.3 g for the PGA period, 0.2 g – 0.5 g for the 0.2-second period, and 0.1 g – 0.4 g for the 1-second period. Meanwhile, the areas with the highest PGA values are Ujung Kulon and Sukabumi Regency, with ranges of 1 g – 1.1 g, 2 g – 2.5 g, and 2 g – 2.2 g for the PGA, 0.2-second, and 1-second periods, respectively. Seismic hazard maps at surface have similar ranges to the bedrock seismic hazard maps, but the increase in PGA values and the spread of the areas are more pronounced for each period. These seismic hazard maps represent surface PGA values because Vs30 data have been included in the calculations. The areas with the highest and lowest PGA values remain the same as in the bedrock maps, but the PGA values have increased compared to the bedrock maps. Amplification maps are created based on the comparison of surface and bedrock maps. These maps show areas with increased PGA values, with amplification values greater than 1 (one), while areas with amplification values less than 1 (one) are referred to as deamplification areas. Generally, the northern part of Java experiences the most significant amplification compared to other regions, reaching 1.6 – 1.8 times for the PGA and 0.2-second periods and 1.6 – 3.3 times for the 1-second period. Meanwhile, deamplification areas are generally located in the central part of Java. Madura generally has the highest amplification values in the western part of the island.